2020
DOI: 10.1080/22221751.2020.1756696
|View full text |Cite
|
Sign up to set email alerts
|

IFITM3 affects the level of antibody response after influenza vaccination

Abstract: Interferon-induced transmembrane protein 3 (IFITM3) as an antiviral factor can inhibit replication of several viruses including influenza virus. A single-nucleotide polymorphism rs12252-C of IFITM3 results in a truncated IFITM3 protein lacking its first 21 amino acids, which is much higher in the Han Chinese population and associated with severe illness in adults infected with pandemic influenza H1N1/09 virus. To investigate if IFITM3 or IFITM3 rs12252-C could affect the antibody response after influenza vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…If functional differences between the examined IFITM3 haplotypes are shown to produce distinct profiles of COVID-19 progression in severe patients, then an improved understanding of the underlying mechanisms may allow more adequate or personalized treatment protocols. Last but not least important, is the need for investigating the examined variant implications in raising an effective immune response after future vaccination against SARS-CoV-2, as it was recently demonstrated that homozygote rs12252:GG, actually reduces the level of antibody response after influenza vaccination (Lei et al, 2020). It could be important to verify whether this also stands for the upcoming SARS-CoV-2 vaccines, and whether a reduced antibody response could be instead elicited in this case by the major allele (rs12252:A), as was suggested throughout our analysis regarding COVID-19 severity.…”
Section: Resultsmentioning
confidence: 99%
“…If functional differences between the examined IFITM3 haplotypes are shown to produce distinct profiles of COVID-19 progression in severe patients, then an improved understanding of the underlying mechanisms may allow more adequate or personalized treatment protocols. Last but not least important, is the need for investigating the examined variant implications in raising an effective immune response after future vaccination against SARS-CoV-2, as it was recently demonstrated that homozygote rs12252:GG, actually reduces the level of antibody response after influenza vaccination (Lei et al, 2020). It could be important to verify whether this also stands for the upcoming SARS-CoV-2 vaccines, and whether a reduced antibody response could be instead elicited in this case by the major allele (rs12252:A), as was suggested throughout our analysis regarding COVID-19 severity.…”
Section: Resultsmentioning
confidence: 99%
“…If functional differences between the examined IFITM3 haplotypes are shown to produce distinct profiles of COVID-19 progression in severe patients, then an improved understanding of the underlying mechanisms may allow more adequate or personalized treatment protocols. Last but not least important, is the need for investigation of the examined variant implications in raising an effective immune response after future vaccination against SARS-CoV-2, as it was recently demonstrated that homozygote rs12252:GG, specifically, is reducing the level of antibody response after influenza vaccination (Lei et al, 2020). It could be important to verify whether this also stands for the upcoming SARS-CoV-2 vaccines, or whether the effect could be the opposite; namely with the reference alleles to be associated with reduced antibody response, as was suggested throughout this analysis regarding COVID-19 severity.…”
Section: Resultsmentioning
confidence: 99%
“…IFITM3 is a kind of ISG. Lei et al reported that the deletion of IFITM3 attenuated the antibody response to influenza vaccination (35). However, no association has been investigated between IQGAP2 and IFITM3.…”
Section: Discussionmentioning
confidence: 99%